PENYUSUNAN RENCANA BISNIS UMKM - Yolanda Masnita; Dida Nurhaida; Hotman Tohir Pohan (JUARA: Jurnal Wahana Abdimas Sejahtera, 2021)
The role of SMEs in supporting the development movement and the Indonesian economy is no longer in doubt. Several times the economic crisis has hit Indonesia, but SMEs can still get through. The flexible nature of SMEs as well as being very vital makes them ideal as an economic driver during difficult situations. But unfortunately, there are still many SMEs that do not have clear and targeted business plans, causing their businesses to not last long. The purpose of community service that will be achieved in this activity is to provide understanding and improve the skills of SMEs actors so that they have the ability to practice compiling business planning and budgets that will be applied to their business, so it is hoped that these SMEs actors can have written guidelines as maps and action plan in running its business. The method used is based on a group approach. The series of activities started from surveys and in-depth interviews to explore problems faced by partners, followed by a coordination meeting of the PkM– community service proposer team to analyze partners' needs and prepare materials. The delivery of material in the form of counseling is carried out online (Zoom meeting), containing: instilling a basic mindset about the importance of making a business plan and the impact of the absence of a business plan, then steps to compile a business plan accompanied by procedures for making a business budget in writing. The material is equipped with examples of business proposals in various business fields so that participants have a clear picture of the form of a business plan. The activity ended with an evaluation of the effectiveness of training through monitoring the implementation of learning outcomes in partners' efforts.